Gong Rénténg Transformation From Sacral to Profan - Suhendi Afryanto; Arthur Supardan Nalan; Gustiyan Rachmadi (Institut Seni Indonesia Denpasar, 2024)
One type of gamelan art that is developing in West Java is Gong Rénténg which used to be often used in sacred ceremonial activities. The sacredness built into the art is inseparable from the belief system adopted by the community as its supporting community. Gong Rénténg's whereabouts then and now are experiencing dynamics of change which are quite important to study, especially his journey which was stopped for various reasons. Stagnant regeneration factors, changes in people's perspectives due to changes in belief systems, as well as the influx of imported arts that continue to intrude on traditional art life, are some of the main reasons this art has experienced ups and downs in its life. The research carried out has the style of cultural research involving key informants as triggers to explore the depth of the material. There are three models of cultural research as approaches taken by researchers, including; Life Story models, Grounded Theory, and Personal Narrative. While the research method used still uses qualitative research by taking locations in two different areas, namely: (1) Ciwaru Village, Cimalaka District, Sumedang Regency, and (2) Kedungsana Village, Plumbon District, Cirebon Regency. In Ciwaru village, the object of research is the art of Gong Rénténg Pusaka Langgeng, while in the village of Kedungsana it is the art of Gong Rénténg Ki Muntili. The results of the research conducted obtained the following information: (1) The Gong Rénténg Pusaka Langgeng art still adheres to adat in a standard way even though the next generation continues to decrease, and (2) The Gong Rénténg Ki Muntili art does two ways to keep it alive, namely ritual ceremonies as part of ancestral traditions are carried out as well as the process of inheritance with new interpretations.